Empowering young minds: Validating the I-DECOBEST module to boost energy literacy, science skills, and attitude for electricity in Standard 5 - Jusoh, Mohd Yahya Fadzli; Ishak, Nor Asniza; Sukardi, Rendi Restiana; Haron, Muhd Zulhilmi (Journal of Islamic, Social, Economics and Development, 2025)
This study evaluates the content validity of the I-DECOBEST module, aimed at enhancing energy literacy, science process skills, and attitudes towards electricity among primary school students. A panel of 7 subject matter experts from various academic fields assessed the module's content using a 10-point Likert scale. Experts evaluated five items related to the module's relevance, feasibility, and potential to meet its educational objectives. The overall content validity score was calculated by dividing the total expert scores by the maximum possible score. The module achieved a content validity score of 88.86%, which is above the accepted threshold of 70%, indicating strong content validity. These findings suggest that the I-DECOBEST module is a well-designed educational tool that aligns with its intended outcomes and is suitable for enhancing energy literacy and science-related competencies in primary education.